Intraspinal bronchogenic cyst: Series of case reports and literature review - Ma, Xueying (J Spinal Cord Med, 2017)
PURPOSE: Spinal bronchogenic cysts (SBCs) are rare congenital lesions. The clinical and imaging characteristics and treatment of SBCs are not well known. We studied three cases of SBCs retrospectively, which were registered in our department and analyzed eight case reports which were all published in English, focusing on providing a deeper knowledge of SBCs. METHODS: Three patients with SBCs registered in our department were retrospectively reviewed. Eight reported SBCs cases published from 1992 to 2015 were enrolled in our study. Imaging diagnosis was confirmed by computed tomography (CT), MRI, and computed tomography angiography (CTA). All of our patients and reviewed cases had undergone surgical resection and the final diagnosis was made by pathological examination. RESULTS: Five lesions were located at the cervical spinal canal. Most patients presented with pain in the limbs and back, which might be related to compression of the spinal cord and the reduced blood supply of the anterior spinal artery. The signal intensity on MRI was correlated with cystic fluid traits to a large extent. Seven lesions were partially removed because of the adhesions to the nearby spinal cord. All reported cases had no recurrence in the later follow-up. CONCLUSIONS: SBCs can occur anywhere in the spinal canal, but they are more likely to present at the cervical canal and might be present along with some developmental malformations of the spine. We emphasize the role of CT and MRI findings in the disease diagnosis. It is recommended that the lesion should be removed as completely as possible.